The impact of new tax policies in semi-subsistence agriculture in the period 2013-2017 - Camelia Toma; Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The paper aimed to estimate the effects of the 2013 new fiscal policy, by broadening the taxation basis of agricultural incomes on almost all types of crops and animal species as well as on small farmers represented by unauthorized and authorized natural persons. Public statistical data of the Ministry of Finance, NAFA (National Agency for Fiscal Administration) and National Institute for Statistics were used, taking into account the specific taxation methodologies and the current legislation, as well as the results of academic research studies and agrarian economy research. The analysis showed that the agricultural income norms, calculated as regional averages and which are flat baseamounts for tax and health insurance contribution calculation, have a decreasing trend due both to the increasing expenditures for agricultural inputs and the decreasing prices of agricultural products. The collection of taxes and health-related contributions based on agricultural income norms has decreased, but one can notice that tax revenues collected for the State Budget from the taxation of rental income increased almost three times during the analyzed period. The increased appetence for agricultural land lease can be attributed on one hand to a lower tax burden than in case of taxing farm incomes of individual exploitation, but on the another hand to the migration phenomenon of young rural labor to Western Europe, while at home only the aging workforce remained, which is forced by the circumstances to lease the arable land.
Keywords: H20; H25; H30; H31; Q14; 330; income norms; rental incomes; tax; health insurance contribution; state budget; agri-food trade deficit; Romania; competitiveness; processed products